Reconstituting the United States' Financial Structure: Some Fundamental Issues - Hyman P. Minsky (Levy Economics Institute of Bard College, 1991)
Deposit insurance, the savings and loan industry, facets of the insurance industry, and a significant number of private banks have all been plagued by recent collapse. The legislative agenda goes beyond merely funding the shortfall in deposit insurance funds: Congress has suggested that reforming the deposit insurance function, as well as the associated regulatory and supervisory structure, is imperative to avoid a recurrence of Treasury financing. An assessment of the problem, and also the prescriptions for a cure, rely on the particular theoretical perspective of the observer. The Smithian view asserts that markets always lead to the promotion of public welfare, while Keynesian theory states that market processes may lead to malfunction of the capital development of the economy-that is, something other than the promotion of public welfare. For example, the crisis in finance during 1991 is largely a delayed response to the experiment in practical monetarism that occurred from 1979 to 1982. In typically simplistic fashion, monetarism suggests that inflation is always the result of too much money chasing too few goods: Hence, controlling inflation rests on controlling money supply. The fundamental flaw in the Bush administration's proposals is that they subscribe to a Smithian theme. They impute the problems afflicting the finance industry (e.g. lack of capital development of the economy) to a minor flaw in the institutional structure rather than to basic characteristics of the economy. The recommendations submitted in the paper are inherently distinct from the administration's proposal and have evolved from a Keynesian model of the economy specifying the processes and determinants of the performance of the economy.
Keywords: 330